An Extensive Research on Knowledge Mining Systems:A Review - Kalaiselvi, K; Sowmiya, J (International Journal of Engineering and Technology, 2018)
With the huge amount of information available, the analysis over the data is the fertile area of knowledge mining research. Knowledge mining is the recent hot and promising research area. Knowledge mining is defined as the process of obtaining relevant knowledge from the pool of resources. In this review paper, we surveyed about the prior works carried out in the knowledge mining systems. We explore the primitives of knowledge mining systems. Attribute imbalance is the primary issue prevails in the knowledge mining process. In the field of higher education, most of the attributes are shared among the data features. In addition a precise introduction to knowledge mining along with its process is presented to get acquainted with the vital information on the subject of knowledge mining systemÂ Â